header bg

Question:

Find the value of 2y(x + z) + 4xz if x = 3, y = 5 and z = 1.

A 52
Explaination

The expression 2y(x + z) + 4xz can be simplified before we substitute the values of the variables x, y and z. We first need to multiply 2y and (x + z).
Step 1: Remove the brackets.
2y(x + z) + 4xz = 2xy + 2yz + 4xz
Step 2: Substitute the values x = 3, y = 5 and z = 1.
2xy + 2yz + 4xz = 2*3*5 + 2*5*1 + 4*3*1
Step 3: Perform the multiplication.
2*3*5 + 2*5*1 + 4*3*1 = 30 + 10 + 12
Step 4: Find the sum.
30 + 10 + 12 = 52